Myelination and mTOR. Issue 4 (6th December 2017) - Figlia, Gianluca; Gerber, Daniel; Suter, Ueli
Abstract: Myelinating cells surround axons to accelerate the propagation of action potentials, to support axonal health, and to refine neural circuits. Myelination is metabolically demanding and, consistent with this notion, mTORC1—a signaling hub coordinating cell metabolism—has been implicated as a key signal for myelination. Here, we will discuss metabolic aspects of myelination, illustrate the main metabolic processes regulated by mTORC1, and review advances on the role of mTORC1 in myelination of the central nervous system and the peripheral nervous system. Recent progress has revealed a complex role of mTORC1 in myelinating cells that includes, besides positive regulation of myelin growth, additional critical functions in the stages preceding active myelination. Based on the available evidence, we will also highlight potential nonoverlapping roles between mTORC1 and its known main upstream pathways PI3K‐Akt, Mek‐Erk1/2, and AMPK in myelinating cells. Finally, we will discuss signals that are already known or hypothesized to be responsible for the regulation of mTORC1 activity in myelinating cells. Main Points: Myelination is metabolically demanding. The metabolic regulator mTORC1 controls differentiation of myelinating cells and promotes myelin growth. mTORC1‐independent targets of the PI3K‐Akt and Mek‐Erk1/2 pathways may also be significant in myelination.